Acute Toxicity Evaluation of the Malagasy Endemic Aloe helenae and A. analavelonensis in Mice - Rokiman Letsara; Rigobert Andrianantenaina; Colette Masengo Ashande; Clarisse Falanga Mawi; M. Yoserizal Saragih; Koto-te-Nyiwa Ngbolua; Baholy Robijaona Rahelivololoniaina (Budapest International Research and Critics University, 2020)
The therapeutic virtues of medicinal plants are known and used in Africa and in Madagascar where natural products form the basis of Traditional Medicine. More than 300 million people worldwide consume dietary supplements and herbal plants. Scientific studies confirm that Aloes contains pharmacologically active ingredients associated with diverse biological activities including fungicidal, antiviral, antibacterial, anti-inflammatory, antimicrobial, laxative, immunomodulating, and anticancer effects. The aim of the present study was to evaluate the effects of orally administered extracts of two Aloe species: A. helenae, A. analavelonensis on mice. Mice were gavaged with crude whole leaves extracts after 24 hours of empty stomach. The extracts administration was found to be not acute toxic at the dose 1200 mg/kg with 100% survival of mice. Since the Aloe helenae is traditionally used against intestinal worms in sheep and goats, it is thus desirable that the plant species could be submitted to phytochemical for the isolation and characterization of new antihelminthic compounds.